Pragmatic multicentre randomised controlled trial evaluating the impact of a routine molecular point-of-care ‘test-and-treat’ strategy for influenza in adults hospitalised with acute respiratory illness (FluPOC): trial protocol - Kate Beard; Nathan Brendish; Ahalya Malachira; Samuel Mills; Cathleen Chan; Stephen Poole; Tristan Clark (BMJ Open)
Background Influenza infections often remain undiagnosed in patients admitted to hospital due to lack of routine testing. When tested for, the diagnosis and treatment of influenza are often delayed due to the slow turnaround times of centralised laboratory PCR testing. Newer molecular systems, have comparable accuracy to laboratory PCR testing, and can generate a result in under 1 hour, making them potentially deployable as point-of-care tests (POCTs). High-quality evidence for the impact of routine POCT for influenza on clinical outcomes is, however, currently lacking. This large pragmatic multicentre randomised controlled trial aims to address this evidence gap.Methods and analysis The FluPOC trial is a pragmatic, multicentre, randomised controlled trial evaluating adults admitted to a large teaching hospital and a district general hospital with an acute respiratory illness, during influenza season and defined by Public Health England. Up to 840 patients will be recruited over up to three influenza seasons, and randomised (1:1) to receive either POCT using the FilmArray respiratory panel, or routine clinical care. Clinical and infection control teams will be informed of the results in real time and where influenza is detected clinical teams will be encouraged to offer neuraminidase inhibitor (NAI) treatment in accordance with national guidelines. Those allocated to standard clinical care will have a swab taken for later analysis to allow assessment of missed diagnoses. The outcomes assessment will be by retrospective case note analysis. The outcome measures include the proportion of influenza-positive patients detected and appropriately treated with NAIs, isolation facility use, antibiotic use, length of hospital stay, complications and mortality.Ethics and dissemination Prior to commencing the study, approval was obtained from the South Central Hampshire A Ethics Committee (reference 17/SC/0368, granted 7 September 2017). Results generated from this protocol will be published in peer-reviewed scientific journals and presented at national and international conferences.Trial registration number ISRCTN17197293